Heavy Metal Pollution in Chapra (Bihar) - Parwez, Akhtar; Ahmad, Jamaluddin (The Scientific Temper, 2022)
River water at 7 sampling sites were examined to evaluate different concentrations of four heavy metals and with using indices also Heavy Metal Pollution Index (HPI); Heavy Metal Evaluation Index (HEI) and Contamination index (Cd) determined in this study. The average concentrations in parts per billion in the increasing order were Cu (292.7)> Fe (309.23) > Mn (475.15) >Zn (3643.9). Resultant average values of HPI 551.40, HEI 12.07 and Cd 8.07 based on metal concentration were obtained.